Overview of Housing Policy Interventions in Poland - Glocker, Daniela (OECD Regional Development Working Papers, 2016)
This paper assesses national public expenditure on housing in Poland, within the context of recent trends in the housing market. It focuses on direct expenditure on housing by the former Ministry of Infrastructure and Development, which until 2016 was the primary ministry charged with housing policy. While Poland has made considerable progress in reducing the housing deficit and improving housing quality, housing affordability and limited diversity of the housing stock remain important policy challenges. A comprehensive and conclusive evaluation of housing policy instruments in Poland is difficult, due to limited relevant data. As such, this paper outlines a series of key questions to guide policy makers in selecting housing policy instruments and in facilitating a more robust framework to measure the efficiency and effectiveness of housing policy instruments